520 Late-Breaking: Effect of Technology on Environmental Emissions from Four Representative U.S. Feedlots and the Beef Production System. (8th October 2021) - Gilreath, Jessica; Rotz, Al; Place, Sara; Thoma, Greg; Wickersham, Tryon
Abstract: Our objective was to evaluate effects of technological management strategies on environmental impacts and net returns of feedlot operations in the United States. Feedlot operations were simulated with the Integrated Farm System Model (IFSM 4.6; USDA-ARS, University Park, PA) to quantify baseline environmental impacts of feedlot production and full US beef cattle production systems. Strategies simulated included: ionophore, implant, ractopamine hydrochloride, combined management (ionophore, implant, and ractopamine hydrochloride; I+I+R), lubabegron, reduced mortality rate, and improved fiber digestion. Days on feed were adjusted whenever necessary and according to production practices typical of commercial feedlots. Subsequently, annual number of cattle finished by the operation was adjusted according to days on feed to maintain consistent one-time capacities. Mitigation strategies were individually modeled and simulated in IFSM for each feedlot operation to calculate intensities (expressed per kg gain) for greenhouse gas (GHG) emissions, fossil energy use, blue water consumption, and reactive nitrogen loss. Additionally, net returns to management were estimated for each feedlot operation. Feedlots were then integrated with simulations of cow-calf, stocker, and backgrounding operations to estimate environmental intensities (expressed per kg carcass weight) for the full beef cattle production system. Carbon emission intensity was reduced most using the I+I+R strategy (10%), followed by implant (6%) and ionophore (5%) strategies alone. Similarly, energy use intensity was reduced the greatest by I+I+R (9%), ionophore (5%), and implants (4%). Reductions in water use intensity were also greatest using I+I+R (9%). Net returns increased for all strategies compared to baseline net return with the greatest improvements observed for I+I+R ($114/finished animal) and implants ($66/animal). Consistent results were observed for all strategies simulated across all four environmental intensities when quantified for the full cattle production system. Implementing I+I+R (7%), ractopamine hydrochloride (4%), and lubabegron (4%) in feedlots resulted in the greatest reductions in environmental emissions.